The woman who rides like a man eaudiobook - Pierce, Tamora (Song of the Lioness, 2006)
A knight at last, Alanna of Trebond heads out to seek adventure in the desert of Tortall. Captured by desert tribesmen, she is forced to prove herself in a magical duel to the death. But her real challenge doesn't come until  after  she wins. As the first female shaman, Alanna must fight to change the ancient traditions of the stubborn desert tribes—for their own sake and for the sake of all Tortall. This third book in the Song of the Lioness quartet continues Alanna's saga as she strikes out alone and discovers herself anew.